"I am different now … I`ve come to understand what coaching is"; an exploration of an Olympic coach`s beliefs and pedagogical practice - Macdonald, S.; Allen, J.; Chapman, R. (Sports Coaching Review, 2025)
Coaching philosophy is an important foundation for coaches` practice and athletes` learning, yet existing literature provides only limited understanding of coaches` philosophy of coaching. This study explored the development of one Olympic coach`s philosophy of coaching and its impact on pedagogical practice. Over six-months, prior to the Tokyo Olympics, we conducted multiple interviews and observations of training sessions involving the coach (Alex) and their three athletes (Chris, Sam and Laurie). Utilising Freirean concepts as a theoretical lens, and employing reflexive thematic analysis, we developed four themes that conveyed Alex`s philosophy development: "We`ve been on quite the journey"; Nudges and self-exploration along the way; Challenges en-route to the Games; and The journey continues. Our analysis helped us to better understand the realities of, and the ad-hoc nature of, developing and practicing meaningful philosophy of coaching within a high-performance programme, which, in turn, impacts and guides the coach`s pedagogical practice.